Analisis Pelaksanaan Otonomi Daerah dan Desentralisasi Pemerintahan dalam Perspektif Undang-Undang 23 Tahun 2014 tentang Pemerintah Daerah - Muhtadin, Muhtadin (Lembaga Yasin AlSys, 2023)
This article aims to examine and describe the application of regional autonomy and decentralization in the governance process in the application of Law Number 23 of 2014 concerning Regional Government. This article was written using a normative legal research method with an emphasis on literature studies related to the decentralization system and regional autonomy. The process of decentralization and regional autonomy is very important to the regional development process in the era of autonomy. What is the role of the central and regional governments in making rules that can accommodate the interests of the community. For this reason, this autonomy is not just the scattering of government administration to achieve government efficiency and effectiveness, but autonomy is interpreted as a constitutional order (staatsrechttelijk), and not just a state administration order (administratiefrechttelijk). Decentralization and regional autonomy regarding the direction of regional general policies basically contain the targets and focus of development policies that will be pursued by regional governments in order to realize regional development agendas and priorities that have been determined based on the vision and mission of the head of the region concerned. This policy direction then needs to be in line with development goals. Therefore, there is a need for synergy between the central and regional governments as a constitutional order which is one unit